A case of combined hepatocellular and cholangiocellular carcinoma with ante mortem diagnosis from image findings - WAKATSUKI, Susumu; OKADA, Shuichi; SUMIDA, Masatoshi; HAYASHI, Gaku; MATSUZAKI, Osamu (Kanzo, 1990)
A case of 79-year-old man with combined hepatocellular and cholangiocellular carcinoma (CHCC) was reported. He was admitted to our hospital because of further exmination of the mass in the epigastric area. On admission, laboratory findings revealed moderate abnormality in his hepatic function and elevation of serum tumor markers such as AFP, CEA, CA19-9 and PIVKA-II. Ultrasonography demonstrated an isoechoic mass with a thin sonolucent rim in the right lobe and an ill-defined mixed-echoic area accompanied by peripheral dilatation of intrahepatic bile ducts in the left lobe. Enhanced X-ray CT showed that the mass in the right lobe was stained by contrast medium. PTC showed that dilated intrahepatic bile ducts of the left lateral segment were almost completely obstructed in the proximal portion. Based on these clinical findings, the ante mortem diagnosis of CHCC (hepatocellular carcinoma in the right lobe and cholangiocellular carcinoma in the left lobe, separately) was made. Although he was treated with the anti-cancer drug, he died of the cancer in 8 months after the diagnosis. The diagnosis of CHCC was confirmed by the autopsy pathologically. It is considered that various imaging modalities make the clinical diagnosis of CHCC possible.